Home mechanical ventilation and specialised health care in the community: Between a rock and a hard place - Nielsen Erik W; Dybwik Knut; Brinchmann Berit S (BMC, 2011)
Abstract Background Home mechanical ventilation probably represents the most advanced and complicated type of medical treatment provisioned outside a hospital setting. The aim of this study was both to explore the challenges experienced by health care professionals in community health care services when caring for patients dependent on home mechanical ventilation, continual care and highly advanced technology, and their proposed solutions to these challenges. Methods Using qualitative research methods, a grounded theory influenced approach was used to explore the respondents' experiences and proposed solutions. A total of 34 multidisciplinary respondents from five different communities in Norway were recruited for five focus groups. Results The core category in our findings was what health care professionals in community health care services experience as "between a rock and a hard place," when working with hospitals, family members, and patients. We further identified four subcategories, "to be a guest in the patient's home," "to be accepted or not," "who decides," and "how much can we take." The main background for these challenges seems to stem from patients living and receiving care in their private homes, which often leads to conflicts with family members. These challenges can have a negative effect on both the community health caregivers' work environment and the community health service's provision of professional care. Conclusions This study has identified that care of individuals with complex needs and dependent on home mechanical ventilation presents a wide range of immense challenges for community health care services. The results of this study point towards a need to define the roles of family caregivers and health care professionals and also to find solutions to improve their collaboration. The need to improve the work environment for caregivers directly involved in home-care also exists. The study also shows the need for more dialogue concerning eligibility requirements, rights, and limitations of patients in the provision and use of ventilatory support in private homes.